Synodontis acanthoperca, a new species from the Ogôoué River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae) - Friel, John P.; Vigliotta, Thomas R. (Zootaxa, 2006)
Synodontis acanthoperca, a new species of mochokid catfish, is described from rapids within the Ogôoué River system of Gabon. This relatively small species (<50 mm SL) is distinguished from all congeners by a distinctive pigmentation pattern that includes a pair of dark patches on the caudal fin and by the presence of hypertrophied opercular spines in sexually mature males.